A coplanar‐electrode direct‐current triboelectric nanogenerator with facile fabrication and stable output. Issue 3 (17th June 2020) - Xu, Guoqiang; Guan, Dong; Yin, Xing; Fu, Jingjing; Wang, Jie; Zi, Yunlong
Abstract: Recently, the direct‐current (DC) TENG based on triboelectrification and discharge has been reported, which can not only generate a DC power, but also provide a higher charge density compared to traditional TENG. Here, we report a novel coplanar‐electrode DC TENG (CDC‐TENG) design which can be easily fabricated by two electrodes, and then a theoretical model is built to illustrate its principle and optimize its output performance. Both theoretical and experimental studies show that the designed device can enhance the energy output, and then the output power is optimized. Furthermore, we develop a three‐electrode CDC‐TENG to output DC during the reciprocating motion. We apply this CDC‐TENG design for rotational energy harvesting and produce a stable constant DC output. This represents an important progress to effectively store the energy harvested by the CDC‐TENG with the aim to drive portable/wearable/implantable electronics with the stable output. Abstract : In this paper, based on the principle of triboelectrification and air breakdown, we design a novel coplanar‐electrode direct current triboelectric nanogenerator (CDC‐TENG), which can be easily fabricated by two electrodes, to generate direct current. This idea is used for rotational energy harvesting which can produce a stable constant direct current.